Accuracy of self-reported height, weight, and waist circumference in a general adult Chinese population. Issue 1 (December 2016) - Lu, Shurong; Su, Jian; Xiang, Quanyong; Zhou, Jinyi; Wu, Ming
Abstract Background Self-reported height, weight, and waist circumference (WC) are widely used to estimate the prevalence of obesity, which has been increasing rapidly in China, but there is limited evidence for the accuracy of self-reported data and the determinants of self-report bias among the general adult Chinese population. Methods Using a multi-stage cluster sampling method, 8399 residents aged 18 or above were interviewed in the Jiangsu Province of China. Information on self-reported height, weight, and WC, together with information on demographic factors and lifestyle behaviors, were collected through structured face-to-face interviews. Anthropometrics were measured by trained staff according to a standard protocol. Results Self-reported height was overreported by a mean of 1.1 cm (95 % confidence interval [CI]: 1.0 to 1.2). Self-reported weight, body mass index (BMI), and WC were underreported by −0.1 kg (95 % CI: −0.2 to 0.0), −0.4 kg/m2 (95 % CI: −0.5 to −0.3) and −1.5 cm (95 % CI: −1.7 to −1.3) respectively. Sex, age group, location, education, weight status, fruit/vegetable intake, and smoking significantly affected the extent of self-report bias. According to the self-reported data, 25.5 % of obese people were misclassified into lower BMI categories and 8.7 % of people with elevated WC were misclassified as normal. Besides the accuracy, the distribution of BMI and WC and their cut-off point standards for obesity of a population affected the proportion of obesity misclassification. Conclusion Amongst a general population of Chinese adults, there was rather high proportion of obesity misclassification using self-reported weight, height, and WC data. Self-reported anthropometrics are biased and misleading. Objective measurements are recommended.